2005
DOI: 10.1128/jvi.79.15.9821-9830.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Reactivation by Phorbol Esters or T-Cell Receptor Ligation Requires both PKCα and PKCθ

Abstract: Latently human immunodeficiency virus (HIV)-infected memory CD4؉ T cells represent the major obstacle to eradicating HIV from infected patients. Antigens, T-cell receptor (TCR) ligation, and phorbol esters can reactivate HIV from latency in a protein kinase C (PKC)-dependent manner; however, it is unknown which specific PKC isoforms are required for this effect. We demonstrate that constitutively active (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 62 publications
3
44
0
Order By: Relevance
“…A similar CD28RE has been identified in the HIV-1 LTR, and accordingly, CD3/ CD28 signal integration is also required for optimal activation of the HIV-1 LTR (67, 68). Trushin et al previously demonstrated that PKC is a central integrative factor for both phorbol ester and TCR/CD28-mediated HIV-1 reactivation in a T cell line (J1.1 cells) (69). NF-B and AP-1 have been identified as the primary targets of PKC, and selective inhibition of certain AP-1 factors by AS601245 could thus differentially influence HIV-1 and cytokine gene expression, in particular, as a functional disparity between cytokine CD28RE and the HIV-1 LTR CD28RE has been described (17).…”
Section: Discussionmentioning
confidence: 99%
“…A similar CD28RE has been identified in the HIV-1 LTR, and accordingly, CD3/ CD28 signal integration is also required for optimal activation of the HIV-1 LTR (67, 68). Trushin et al previously demonstrated that PKC is a central integrative factor for both phorbol ester and TCR/CD28-mediated HIV-1 reactivation in a T cell line (J1.1 cells) (69). NF-B and AP-1 have been identified as the primary targets of PKC, and selective inhibition of certain AP-1 factors by AS601245 could thus differentially influence HIV-1 and cytokine gene expression, in particular, as a functional disparity between cytokine CD28RE and the HIV-1 LTR CD28RE has been described (17).…”
Section: Discussionmentioning
confidence: 99%
“…PKCa is proposed to act in concert and/or in alternative pathways with PKCh to regulate the IkB/NFkB axis (Trushin et al, 2003); it has additional functions including HIV reactivation (Trushin et al, 2005), TCR downregulation (von Essen et al, 2006) and granule exocytosis (Grybko et al, 2007). PKCa-deficient mice have a severe defect in the Th1 response and IFNc secretion (Pfeifhofer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In acutely infected cells, prostratin enhances cell survival possibly due to cytostatic effects (18). Most importantly, in latently infected cells, prostratin stimulates viral replication putatively through PKC-mediated phosphorylation of IκB kinase, which enables release and penetration of the transcription factor NF-κB into the cell nucleus (26), where its binding to the HIV LTR leads to viral gene expression and subsequent replication of the virus.…”
mentioning
confidence: 99%